Моделирование термонапряженного состояния двухопорного замкового соединения лопаток паровой турбины - Гармаш, Н. Г. (НТУ "ХПИ", 2006)
The task of termocontact interaction for lock connection as the first stage of low pressure of the turbine K-300-240-2 is consider. Is shown, that the registration of temperature strains unessentially influencing on a level of contact pressure, strengthens non-uniformity of its distribution. That it is necessary to take into account at an estimation of functionability of constructions
Keywords: замковые соединения лопаток; турбомашины; температурные деформации; тепловой удар